Study of the impact of different salts on the intrinsic dissolution rate of pharmaceutical compounds - Karl Box; Rebeca Ruiz; Breeze Outhwaite; Sam Lee (University of Huddersfield Press, 2017)
The intrinsic dissolution rate (IDR) of a free base and its four salts were investigated with the aim of selecting the salt with the best dissolution performance. IDRs were measured using the Sirius inForm platform with quantitation by in-situ UV spectroscopy. Results showed that the hydrochloride salt had the highest dissolution rate followed by the maleate and p- toluenesulphonate salts, whilst the naphthalene-2-sulphonate and free base had the lowest IDR values. The Sirius inForm provides valuable insights into the dissolution behaviour of different drug forms during salt selection.